2022
DOI: 10.1186/s13071-022-05479-1
|View full text |Cite
|
Sign up to set email alerts
|

Assigning Culicoides larvae to species using DNA barcoding of adult females and phylogenetic associations

Abstract: Background Orbivirus-induced hemorrhagic diseases cause high mortality in wild and captive white-tailed deer in North America. The role of different Culicoides species in Orbivirus transmission outside of areas of intensive animal production has not been established. At our study location, bluetongue virus (BTV) RNA-positive female Culicoides debilipalpis pools have been detected annually since 2012 when BTV transmission was noted in a captive deer herd. Identifying specific larval habitats of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…In our entomological surveys, we found that Triatoma spp. nymphs, which are difficult to identify morphologically, could be identified by DNA barcoding, similar to what has been utilized for the molecular identification of immature Culicoides biting midges [34]. Past entomological surveys of the four primary domestic triatomines of this region, T. dimidiata, T. mazzotti, T. pallidipennis, and T. phyllosoma, in 1980 documented their occurrence in 24 municipalities [17]; however, Ramsey et al (2000) [12] conducted a study between 1996-1998 and reported eight species of triatomines in 64 municipalities [12].…”
Section: Discussionmentioning
confidence: 99%
“…In our entomological surveys, we found that Triatoma spp. nymphs, which are difficult to identify morphologically, could be identified by DNA barcoding, similar to what has been utilized for the molecular identification of immature Culicoides biting midges [34]. Past entomological surveys of the four primary domestic triatomines of this region, T. dimidiata, T. mazzotti, T. pallidipennis, and T. phyllosoma, in 1980 documented their occurrence in 24 municipalities [17]; however, Ramsey et al (2000) [12] conducted a study between 1996-1998 and reported eight species of triatomines in 64 municipalities [12].…”
Section: Discussionmentioning
confidence: 99%
“…[32,33]. This method proves to be difficult for the identification to the species level of females of closely related species that have very similar or identical (isomorphic) features and is even more challenging for juvenile specimens (larvae, pupae) [34][35][36], for which either identification keys have not yet been developed or distinguishing features are not yet even established for corresponding adults. Furthermore, morphological species identification cannot be used for the determination of phylogenetic distances [37] and may require time-consuming analyses of slide-mounted microscopical insect preparations to visualize fine structures [38], a lot of practical experience and fresh material with distinct coloration.…”
Section: Introductionmentioning
confidence: 99%
“…The potential for molecular identification methods to help address these issues, allowing non‐typical semaphoronts to contribute to studies in biodiversity inventory and systematics, has been recognized since DNA sequences first became readily accessible (Caterino et al, 2000; Stern et al, 1997). Associations of larvae through DNA sequencing have become routine (Ahrens et al, 2007; Caterino & Tishechkin, 2006; Curiel & Morrone, 2012; Jin et al, 2022; Miller et al, 2005; Sinclair et al, 2022; Zhou et al, 2007). A number of authors have also demonstrated successful associations of sexes in dimorphic species (Corley & Ferreira, 2017; Ekrem et al, 2010; Ferreira & Ivie, 2022; Gariepy et al, 2022).…”
Section: Introductionmentioning
confidence: 99%